ERK Phosphorylation Regulates Sleep and Plasticity in Drosophila. - Vanderheyden, W.M.; Gerstner, J.R.; Tanenhaus, A.; Yin, J.C.; Shaw, P.J. (PLoS ONE, 2013)
Given the relationship between sleep and plasticity, we examined the role of Extracellular signal-regulated kinase (ERK) in regulating baseline sleep, and modulating the response to waking experience. Both sleep deprivation and social enrichment increase ERK phosphorylation in wild-type flies. The effects of both sleep deprivation and social enrichment on structural plasticity in the LNvs can be recapitulated by expressing an active version of ERK (UAS-ERK(SEM)) pan-neuronally in the adult fly using GeneSwitch (Gsw) Gsw-elav-GAL4. Conversely, disrupting ERK reduces sleep and prevents both the behavioral and structural plasticity normally induced by social enrichment. Finally, using transgenic flies carrying a cAMP response Element (CRE)-luciferase reporter we show that activating ERK enhances CRE-Luc activity while disrupting ERK reduces it. These data suggest that ERK phosphorylation is an important mediator in transducing waking experience into sleep.